H2 Production from Formic Acid Using Highly Stable Carbon-Supported Pd-Based Catalysts Derived from Soft-Biomass Residues: Effect of Heat Treatment and Functionalization of the Carbon Support - Jessica Alejandra Chaparro-Garnica (MDPI AG, 2021)
The production of hydrogen from liquid organic hydrogen carrier molecules stands up as a promising option over the conventional hydrogen storage methods. In this study, we explore the potential of formic acid as a convenient hydrogen carrier. For that, soft-biomass-derived carbon-supported Pd catalysts were synthesized by a H3PO4-assisted hydrothermal carbonization method. To assess the impact of the properties of the support in the catalytic performance towards the dehydrogenation of formic acid, three different strategies were employed: (i) incorporation of nitrogen functional groups; (ii) modification of the surface chemistry by performing a thermal treatment at high temperatures (i.e., 900 °C); and (iii) combination on both thermal treatment and nitrogen functionalization. It was observed that the modification of the carbon support with these strategies resulted in catalysts with enhanced performance and outstanding stability even after six consecutive reaction cycles, thus highlighting the important effect of tailoring the properties of the support.